The Calcium Rhythms of Different Cell Types Oscillate with Different Circadian Phases - Wood, Nicola T. (American Society of Plant Physiologists, 2001)
Transgenic tobacco (Nicotiana plumbaginifolia) seedlings containing the Ca(2+)-sensitive luminescent protein aequorin have been shown to exhibit circadian variations in cytosolic calcium. Concomitant measurements of cytosolic and nuclear calcium show that circadian variations in the cytoplasm are not expressed in the nucleus. To investigate whether all cells of transgenic seedlings contribute equally to circadian variations in cytosolic calcium, different promoters eliciting different expression patterns have been placed upstream of aequorin and used for transformation. The circadian peak occurred at different times in the three transgenic lines constructed. Luminescence imaging of these transgenic lines indicated that aequorin was differentially accumulated among the main tissues and cells of the seedlings and overcoat technology with applied epidermal strips indicated that the surface cell layers contribute the vast majority of luminescent light. We conclude that the Ca(2+) rhythmicities of cells and tissues oscillate with distinct differences in phase, that this might represent different underlying cellular control mechanisms and that these observations have significant implications for our understanding and study of Ca(2+) mediated signal transduction in plant cells.